Occurrence and Assessment of Chemical Contaminants in Drinking Water in Tunceli, Turkey - Demir, Veysel; Ergin, Sezai (Journal of Chemistry, 2013)
The objective of this study was to analyze drinking water samples from 21 sites in the city center and seven municipalities of Tunceli, Turkey, in order to determine the presence of nitrate, nitrite, fluoride, bromate, pesticides, polycyclic aromatic hydrocarbons (PAHs), trihalomethanes (THMs), and some other chemicals. In all locations, the concentrations of chemicals investigated were below the permissible limits set by local and international organizations for drinking water. Low levels of nitrate (4.79 ± 4.20 mg/L), fluoride (0.11 ± 0.08 mg/L), and THMs (6.63 ± 5.14 μg/L) were detected in all locations. A low level of tetra, chloroethane, which is suspected to be a human carcinogen, was also detected in 8 locations in the range of 0.26–0.43 μg/L. These contaminants may pose adverse health effects or minimum hazard due to long-term exposure. In all locations, bromate, benzene, total PAH, 1-2 dichloroethane, vinyl chloride, acrylamide, and epichloridine levels in drinking water samples were under detection limits.